Conjunctival changes induced by prostaglandin analogues and timolol maleate: a histomorphometric study - Russ,Heloisa Helena Abil (2007)
PURPOSE: To compare histological changes induced by antiglaucoma medications in the rabbit conjunctiva. METHODS: Fifty New Zealand rabbits were divided in 5 groups of 10 animals. The left eyes were treated daily with one drop of bimatoprost 0.03%, travoprost 0.004%, latanoprost 0.005%, timolol maleate 0.5% or artificial tears containing benzalkonium chloride (BAK) for 30 days. The right eyes served as controls. Superior limbic conjunctival biopsies were performed at the 8th and 30th day in 5 rabbits of each group. The conjunctiva was fixed with 10% formaldehyde, followed by HE and PAS staining. Morphohistometric quantitative analyses were performed to evaluate the following parameters: inflammatory infiltrate, epithelial thickness, number of goblet cells, diameter and number of blood vessels. RESULTS: At the 8th and 30th posttreatment days, all groups, except one that received artificial tears, exhibited a diffuse inflammatory infiltrate, composed by lymphocytes and neutrophils, which was denser in the timolol group than in the prostaglandin (PG) analogues groups. At the 30th day, the timolol group also showed an increased subepithelial collagen density and a significant increase in epithelial thickness (p=0.0035). The goblet cell density was significantly increased at the 8th day in the group treated with travoprost (p=0.0006), and at the 30th day in those treated with bimatoprost (p=0.0021) and latanoprost (p=0.009). CONCLUSIONS: Although a moderate, diffuse inflammatory infiltrate was observed in PG-treated eyes, no changes in conjunctival epithelial thickness or subconjunctival collagen density were observed with these medications, suggesting that these drugs induce fewer changes than timolol maleate in the rabbit conjunctiva.